Change of Position of Constitutional Judiciary - Orlović, Slobodan Petar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
constitutional judiciary is the youngest branch of authority in the horizontal level of state power. Constitutional judiciary has, during its existence – during two centuries as an ordinary court and during one century as a special authority, changed its position, role and importance. Those characteristics of constitutional judiciary had an increasing way - the position became better, in political and law sense, its role has expanded and the importance has increased. Today, constitutional judiciary is an inevitable subject of constitutional regimes in huge number of states (between them are almost all federations) but, in the same time, constitutional judiciary is an authority which is at least limited by the constitution. The constitution is “soft” to the constitutional judiciary because the judiciary interpreted the constitution in accordance to its political and law attitudes, hidden by the guise of protection. Different separation of power, a rise of executive power, requests for better protections of fundamental human rights, a changed role of state and executive power, altogether, have influenced to change of position of constitutional judiciary.